Warrantless search and seizure in terms of the Drugs and Drug Trafficking Act Criminal Procedure Act and South African Police Services Act : a comparative analysis with Canadian law - De Villiers, Wium P. (University of Pretoria, 2017)
Mini Dissertation (LLM)--University of Pretoria, 2017.